Roles of IL‐2 in bridging adaptive and innate immunity, and as a tool for cellular immunotherapy. Issue 1 (1st June 2020) - Bendickova, Kamila; Fric, Jan
Abstract: IL‐2 was initially characterized as a T cell growth factor in the 1970s, and has been studied intensively ever since. Decades of research have revealed multiple and diverse roles for this potent cytokine, indicating a unique linking role between adaptive and innate arms of the immune system. Here, we review the literature showing that IL‐2 is expressed in a plethora of cell types across the immune system, where it has indispensable functions in orchestrating cellular interactions and shaping the nature and magnitude of immune responses. Emerging from the basic research that has revealed the molecular mechanisms and the complexity of the biologic actions of IL‐2, several immunotherapeutic approaches have now focused on manipulating the levels of this cytokine in patients. These strategies range from inhibition of IL‐2 to achieve immunosuppression, to the application of IL‐2 as a vaccine adjuvant and in cancer therapies. This review will systematically summarize the major findings in the field and identify key areas requiring further research in order to realize the potential of IL‐2 in the treatment of human diseases. Abstract : Review on IL‐2 in adaptive and innate immunity and its potential applications in immune therapies.